Buitebladontwerpe as bydrae tot teksinterpretasie van Breyten Breytenbach se Buffalo Bill in die Ongedanste dans - Morkel, Anita (My University, 1992)
In his text production the co- producer must realize a total text. It holds good especially in the case of Breyten Breytenbach whose paint- work is printed on the cover designs of his texts. An integrated text interpretation is only possible if the relation between the visual and verbal text is examined. The text signs in the cover design of buffalo bill as "die tweede bundel" in the volume series die ongedanste dans indicates an iconic connection with the verbal text contents. The relation is in the text signs (the colour symbols, the indices and icons), the mode of work and coding's contained therein. The creative co-production of the total text is brought about visually by an iconic coding of the experience of the big Void, the hiatus, the enso (in Japanese). The hiatuses make the transformation of all the text signs possible so that the political, religious, sexual and Breytenbach's airs poetical coding's therein overlap one another. The cover designs of buffalo bill and also the other volumes in die ongedanste dans are a visualizing of the hiatuses in which this dynamic transformation process can take place. Thus the text signs in the cover designs of die ongedanste dans are a cryptic expression of the coding's and mode of work in force. The co-producer's normal expectations about text components are perpetually de construed in the hiatuses and at the same time also construed to form new perspectives. All the infinite possibilities that are gradually discovered, lead to insight, satori so that the text components' true context can be seen. The message that the co-producer can bring to himself, is situated in a consciousness of a continues collapse and reconstruction, of structures. The cover design of buffalo bill is a cryptic expression of a ceaseless redefining of absolutely everything.
Thesis (MA)--PU for CHE, 1992.